1999
DOI: 10.1111/j.1365-2621.1999.tb15938.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Bacillus cereus on Oil‐blanched Potato Strips for “Home‐style” French Fries

Abstract: Fresh cut, oil blanched strips from whole potatoes stored at 7 or 13 °C were inoculated with approximately 3 or 5 log CFU/g Bacillus cereus and incubated at 21 or 26.7 °C for up to 9 h to model handling of "home-style" French fries. Whole potato storage at 13 °C and incubation at 26.7 °C resulted in faster growth than 7 or 21 °C. Frying (2 to 3.5 min at 185 °C) inactivated up to 5.1 log B. cereus spores. Oil blanched potato strips for "home-style" French fries should be stored at £ 21 °C or finish fried or dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many researchers have reported that B. cereus is the pathogen that contaminates both raw (9) and processed meat products (10), because this pathogen is ubiquitous, spore forms and highly resistant to adverse conditions such as heat and dehydration (11). In our research, the range and mean ± SE of B. cereus were 0.7-5.6 and 2.0 ± 0.62 CFU/g respectively.…”
Section: Discussionmentioning
confidence: 72%
“…Many researchers have reported that B. cereus is the pathogen that contaminates both raw (9) and processed meat products (10), because this pathogen is ubiquitous, spore forms and highly resistant to adverse conditions such as heat and dehydration (11). In our research, the range and mean ± SE of B. cereus were 0.7-5.6 and 2.0 ± 0.62 CFU/g respectively.…”
Section: Discussionmentioning
confidence: 72%
“…Research by Doan and Davidson (1999) demonstrated that B. cereus was capable of growth on oil-blanched potato strips held at 26.7 °C. The behavior of S. aureus in that product has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…cereus is difficult to eliminate from foodstuffs and food-processing systems because it forms spores that are ubiquitous and highly resistant to adverse conditions such as heat, dehydration, and other physical stresses (Andersson, 1995; Doan and Davidson, 1999;Larsen and Jør-gensen, 1999 In this study, we examined the growth patterns and toxigenicity of B. cereus in foodstuffs of animal origin, such as ham and cheese, in RTE sandwiches and Kimbab, and analyzed these ingredients to identify the major sources of B. cereus contamination and thereby improve the management of B. cereus contamination of RTE foods.…”
Section: Introductionmentioning
confidence: 99%